Pathways to past ways: a positive approach to routeways and mobility. (October 2020) - Bell, Martin; Leary, Jim
Abstract: Abstract : Past trackways and the mobility associated with them have long been a neglected topic of research in Britain—a lack of attention attributable to the publication of Alfred Watkins's The old straight track in 1925. Yet, new interdisciplinary approaches, including from the perspectives of social theory and the sciences, can allow us to move forward. Here the authors offer the first steps towards a positive approach to understanding past mobility.